Akibat Hukum dan Dampak Psikologis Perkawinan Siri bagi Perempuan dan Anak-Anaknya: (Kajian Teoretis Menurut Undang-Undang dan KHI) - Catur Rohman Kusmayadi, Rudy; Madarik, Muhammad (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2020)
Marriage is the gate of life that is usually passed by mankind in carrying out life as husband and wife. Allah SWT create something with pairs, male and female, male and female (of animals), day and night, and so on. The Siri marriage still occur nowadays. In fact, unregistered marriage such as Siri marriage could create disadvantage influence on women and their children. The siri marriage, or known by 'married under the hands', 'kawin siri' or 'nikah siri', is a marriage that is carried out based on religious rules or customs, but it is not registered in the official marriage affair (KUA).. Even though it is legal according to religion, marriage under the hand or the Siri marriage has no legal protection from the law affairs. So that, Indonesia official law cannot provide legal protection for women and their children when they have any marriage issue. Moreover, if the marriage issue would affects women and children’s psychological problems. Keywords: The Siri marriage, legal consequences, psychological impact.